(untitled) (Research, Society and Development, 2022)
Introduction: Fibromyalgia is classified as a rheumatologic syndrome of clinical diagnosis based on the patient’s complaint regarding the presence of diffuse pain, without trauma, noninflammatory, associated with cognitive and sleep disorders, as well as fatigue and stiffness. Described as the second most commonly found diagnosis in rheumatologic diseases, it triggers a negative impact on patients’ functional capacity due to the complexity of its etiopathogenesis and its sequelae. Epidemiological data of this disease in patients from northern Brazil are nonexistent. General Objective: To outline the epidemiological profile of fibromyalgia in patients diagnosed at the rheumatology referral department of Gurupi-TO. Materials and Methods: We selected women aged 18 to 75 years, with a medical diagnosis of fibromyalgia. Through interviews, they answered the epidemiological survey questionnaires (with characterization of the sociodemographic profile and history of the disease) and level of disability (QIFR-Br). Results: The fibromyalgic sample from Southern Tocantins State presented an epidemiological profile and level of disability similar to the rest of Brazil, characterized by: women, with low education and high level of pain intensity and disability.